Investor taxes and equity pricing: Using income trusts in a cross-sectional analysis - Kenneth Klassen; Devan Mescall (Canadian Tax Journal, 2012)
Adapting a valuation model, the authors create an after-tax Feltham-Ohlson model to gain deeper insights into the effect of both investor- and corporate-level taxes on equity valuation. We apply this model to the unique Canadian setting of income trusts to explore the valuation effect of taxes and the tax characteristics of investors. Canadian income trusts are publicly traded flowthrough entities whose use expanded beyond the traditional real estate sector. Their unique tax status and broad usage across industries provides an opportunity to investigate the role of investor taxes on common shares in a cross-sectional analysis. Empirical testing shows that the value of earnings is lower for corporations than for a set of matched businesses operating as an income trust, consistent with the average investor in an income trust having a tax rate significantly below the top marginal individual rate.